Penerapan Framewoork Vue JS dalam Pembuatan GPS Tracking Truk Peron Kelapa Sawit Berbasis Website - Antoni Pribadi; Nofiar. Am, Andri; Nurfitriani, Desi (Politeknik Negeri Bengkalis, 2023)
Indonesia is one of the world's palm oil producers whose selling value has increased in the last decade, palm oil production is a sector that is relied on and provides very wide employment opportunities. To maintain the quality of palm oil, procedures and operations are needed in managing oil palm. There are several obstacles that often occur, including the lack of supervision of the transportation process, the low absorption of technology use, and the high sales of palm fruit bunches. The research objective was carried out as an effort to increase the productivity of the transportation fleet, namely by implementing the Global Positioning System. This is done to improve timeliness, maintain driver work discipline, and know the vehicle's position in real time using GPS Tracking. This study uses research methods ranging from analysis to testing and uses Vue Js as a framework for creating interfaces on websites. The components of the tools used are GPS Neo M8N, NodeMCU ESP32, and GSM SIM800L. Running the tool uses the Neo M8N GPS which gets an internet network from GSM SIM800L to send the coordinates of the palm oil trucks through the website. The results of this study are in the form of a website displaying the location of trucks, this study received positive responses from users who stated that this system can improve security, manage transport time, and can monitor trucks in real time.